Encyclopedia of information science and technology - Khosrow-Pour, Mehdi, 1951- (Hershey, PA : Information Science Reference, 2015)
"This 10-volume compilation of authoritative, research-based articles contributed by thousands of researchers and experts from all over the world emphasized modern issues and the presentation of potential opportunities, prospective solutions, and future directions in the field of information science and technology"--
Includes bibliographical references and index.
oif 24/06/15
Ref.
Keywords: Information science -- Encyclopedias; Information technology -- Encyclopedias